3-D numerical simulation of the tidal circulation in the Gulf of Tonkin, Vietnam - Vinh, Phan Ngoc; Dan, Nguyen Kim (Vietnam Journal of Mechanics, 2001)
The purpose of this paper is to present 3-D numerical simulation of the tidal circulation in the Gulf of Tonkin. A sigma-coordinate system transformation is used to make possible a total fitting between the computing point-grid and the bottom topography as well as the free water surface. A turbulence-closure sub-model K-L which permits the parameterization of the turbulence mixing is also included. The studied domain, the whole Gulf of Tonkin, extends from the coastal zone of Quang-Ninh into Thua Thien Hue province and as far as Hai-Nam (China) island seawards. The model have been calibrated and verified by the observed data at six different stations for a three and seven-day periods. The results are in good agreement with the observed data. The kinetic energy distribution was considered